The Anatomy of Viral TikTok Ads: Sentiment and Semantic Analysis of Top-Performing Keywords - Koswara, Asep (Devitara Innovations, 2024)
This study analyzed the anatomy of viral TikTok advertisements by examining the sentiment and semantic characteristics of top-performing keywords in the Indonesian market. The research utilized data from TikTok’s Keyword Insights platform, focusing on metrics such as popularity, click-through rate, conversion rate, and cost per acquisition. The analysis revealed that viral keywords predominantly exhibited neutral sentiment and were closely linked to culturally relevant terms reflecting local consumer interests. The dataset included over 700 million impressions and revealed that keywords such as pria (man), diskon 50% (50% discount), and sepatu (shoes) dominated virality with popularity scores reaching up to 40,000 and engagement rates exceeding 25%. Sentiment analysis showed that all top viral keywords carried a neutral sentiment. Correlation analysis indicated a strong positive relationship (r = 0.94) between engagement metrics and virality, while click-through rates negatively correlated with virality (r = -0.54). Cultural factors, including keywords related to modest fashion like hijab (headscarf) and gamis (muslim dress), were significant in shaping consumer behavior. The study demonstrates that viral success on TikTok in Indonesia relies on a combination of semantic relevance, cultural context, and interactive engagement, providing strategic insights for data-driven and culturally tailored marketing campaigns.